Correlative Microscopy and Spectroscopy Workflow for Microplastics - Sarau, George; Kling, Lasse; Oßmann, Barbara; Unger, Ann Katrin; Vogler, Frank; Christiansen, Silke H. (Applied spectroscopy, 2020)
Microplastics (MPs) have been reported in various environmental compartments and their number is continuously increasing because of degradation into smaller fragments down to nanoplastics. Humans are exposed to these small-sized MPs through food and air with potential health consequences that still need to be determined. This requires, in the first place, efficient and detailed visualization, relocalization, and characterization of the same MPs with complementary analytical methods. Here, we show the first application of a correlative microscopy and spectroscopy workflow to MPs that meets these demands. For this purpose, standard MP particles on aluminum-coated polycarbonate membrane filters were investigated by an optical zoom microscope and a hyphenated scanning electron microscopy (SEM)-Raman system. By merging the obtained data in one software, it is possible to navigate on the entire filters’ surface and correlate at identical locations MP morphology at the spatial resolutions of electron (1.6 nm at 1 kV for the used SEM, ∼100 nm minimum MP size in this study) and optical (∼1–10 µm) microscopies with chemical identification by micro-Raman spectroscopy. Moreover, we observed that low-voltage SEM works without a conductive coating of MPs, causes no detectable charging and structural changes, and provides high-resolution surface imaging of single and clustered MP particles, thus enabling subsequent Raman measurements. We believe that further work on the accurate identification and quantification of micro- and nanoplastics in real samples can potentially profit from this workflow.
CRIS-Team Scopus Importer:2020-08-14
Keywords: correlative workflow; Microplastic; microscopy; nanoplastic; Raman; scanning electron microscopy; SEM; spectroscopy